Structure and properties of nanocomposite films based on sodium caseinate and nanocellulose fibers - Pereda, Mariana (2011)
Films made from sodium caseinate and nanocellulose were prepared by dispersing the fibrils into film forming solutions, casting and drying. Composite films were less transparent and had a more hydrophilic surface than neat sodium caseinate ones. However, the global moisture uptake was almost not affected by filler concentration. Addition of nanocellulose to the neat sodium caseinate films produced an initial increase in the barrier properties to water vapor, and then, it decreases as filler content increased. This was explained in terms of additional detrimental changes (cracks and bubble formation) induced in the morphological structure of the film by the reinforcement. The tensile modulus and strength of composite films increased significantly with increasing cellulose concentrations, while the values of elongation decreased. In the same way it was found that the storage modulus increases considerably with filler addition in the low temperature range (<60 °C), though the effect of temperature on the films performance is even more dramatic, as expected in protein-based materials.